Digital ethnicity: discussion of a concept and implications for education - Adams, Nan B.; DeVaney, Thomas A. (EAI Endorsed Transactions on e-Learning, 2011)
Interaction with the rapidly expanding digital technologies for education, work, and play has drastically changed the processes and practices of world populations. As societies evolve in response to these new communication and calculation tools, the need arises to understand the sometimes unique but increasingly common change in cultures. The Digital Ethnicity Scale (DES), utilizing Longstreet’s (1978, Aspects of Ethnicity (New York: Teachers College Press) model of the Aspects of Ethnicity, was developed to describe the emergence of new cultural patterns of behavior that result from the influence of human interaction with digital communication technologies (Adams, DeVaney, and Longstreet (2010) Comput. Hum. Behav. 26(6): 1822–1830). Longstreet’s definition of ethnicity focuses on cultural development during the earliest stages of human development, prior to the onset of children’s abstract thinking. The ultimate goal for the development of the DES is to describe those aspects of digital ethnicity and collect these descriptions along with demographic data to achieve profiles of various digital ethnicities. A discussion of the guiding concept and overview of the development of the DES seeks to present a description of these digital ethnic profiles that may provide insight into the educational needs of rapidly changing societal groupings with hopes of providing guidance for educational practice.